The “Doctrine” of Law in Israel - Levin, Natali (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
This article examines the doctrine of law in Israel, highlighting the integration of various legal influences, particularly the significant role of British legal traditions in shaping the legal framework. Despite the absence of a formal written constitution, Israel’s Basic Laws serve as a constitutional foundation that guides governance and protects individual rights. The legal system reflects a unique blend of the Jewish law, the British common law, and modern statutory law, creating a dynamic and distinctive legal framework. The article provides a comparative analysis of Israel’s legal system in relation to the British law and the Jewish law, emphasising the implications of not having a singular constitution and the importance of the Basic Laws in safeguarding rights. Overall, the article contributes valuable insights into the complexities of Israel’s legal landscape, particularly the balance between secular and religious influences, making it relevant for scholars, practitioners, and those interested in the intersection of law and society.